Alternative finance: a historical perspective. (August 2019) - Chambers, David; Saleuddin, Rasheed; Mcmahon, Craig
Abstract: Innovations in the world of alternative finance such as online consumer lending, fund-raising platforms and cryptocurrencies are proceeding apace. In this article, we examine three historical case studies of newly emerged non-bank financial markets and discuss the possible implications for today's alternative finance markets. The first insight is that the private sector can generally be counted on to meet previously unmet needs. Moneylenders filled a gap unaddressed by the banking system of the day. Junior market IPOs provided access to funds for smaller companies that might otherwise have struggled to raise external finance. Private currencies replaced sovereign coins in transactions at various points in history. The second insight, however, is that new financial markets and instruments eventually attract the attention of regulators. Finally, these examples are a warning to industry not to take for granted that an initially laissez-faire regulatory regime precludes a stronger response at some point in the future. In all three cases, tougher regulation – in some cases even to the point of shutting down the products and markets concerned – arrived after long periods of observation and deliberation by the state.